Integrating Bahsul Kutub To Enhance The Quality of Santri Education at Fadlun Minallah Islamic Boarding School - Umi Habibah; Sutrisno (YPI Ulul Albab, 2026)
Improving the quality of learning in Islamic boarding schools is essential to ensure that Islamic scholarly traditions remain relevant amid developments in modern education. This study analyzes how the integration of Total Quality Management (TQM) principles into the Bahsul Kutub program can strengthen educational quality at Fadlun Minallah Islamic Boarding School. Using a qualitative approach involving observation, interviews, and document analysis, the study examines the roles of leadership and academic governance, as well as the dynamics of the Bahsul Kutub forum, in developing a culture of quality within the pesantren. The findings indicate that applying TQM principles—including visionary leadership, continuous improvement, human resource development, and process management—makes the implementation of Bahsul Kutub more systematic and effective. The program not only preserves the tradition of studying classical Islamic texts but also functions as a learning strategy that improves santri literacy in the kitab kuning, analytical competence, and critical-thinking skills. Its positive effects are evident in enhanced academic quality, intellectual development, a stronger scholarly character, and santri achievements in the Musabaqah Qira’atul Kutub (MQK) competition. This study confirms that integrating TQM and Bahsul Kutub offers a promising model for strengthening the quality of pesantren education. Future research should develop quantitative instruments for critical evaluation and compare the effectiveness of this model across different Islamic boarding schools.